A Generalized Stationary Algorithm for Resonant Tunneling: Multi-Mode Approximation and High Dimension (Communications in Computational Physics, 2011)
The multi-mode approximation is presented to compute the interior wavefunction of Schrödinger equation. This idea is necessary to handle the multi-barrierand high dimensional resonant tunneling problems where multiple eigenvalues areconsidered. The accuracy and efficiency of this algorithm is demonstrated via severalnumerical examples.